Logiczne aspekty języka a teksty humorystyczne Rola mechanizmu logicznego w dowcipach - Brzozowska, Dorota (Investigationes Linguisticae, 2012)
"The objective of this paper is a presentation of the relations between the logical aspects of a language and the study of jokes. The linguistic material used in sample analyses comprises modern texts about mathematicians which render the specific way of thinking attributed to this group within joke stereotypes. Bearing in mind that humour is frequently connected with creativity and an ability to depart from patterns, we should assume that when humorous texts are creative and break the rules, when they are inconsistent with standards and exceptional - and thus illogical - they fulfil their ludic purpose very well. Another fundamental issue is the existence and function of so-called nonsense humour which - being contrary to the principles of logic - constitutes a separate whole. Its distinction would imply that the remaining types of humorous texts are rational, that is logical. Thus humour may be both logical and illogical. The main objective of this paper is search for an answer to the question whether the logical mechanism is obligatorily present in every type of humour. "